Strength of steel pipelines in corrosive sites with repair composite bandage - Vereshchaka, Serhii; Mukoseev, Volodymyr; Rohovyi, Stanislav; Tsyhanenko, Hennadii (Academic journal Industrial Machine Building Civil Engineering, 2022)
During operation, defects may appear on the surface of local sections of steel pipelines due to corrosion or adhesive wear, reducing their strength, and sometimes, unfortunately, leading to an accident of the entire pipeline. The use of repair bands made of innovative composite materials is one of the promising areas for maintaining the working pressure of steel pipelines. The task of this work is the development of the method for determining the destructive hydrostatic pressure of repair bands made of composite innovative materials. The obtained theoretical results and experimental studies made it possible to choose the strength criterion and determine the values of the ultimate stresses at the junction points of the bands' composite tire and the steel pipe.
Keywords: composite materials; local defects; repair bandage; steel pipelines